A study on affcetive factors that contribute to communication apprehension in ESL classroom / Norhartini Aripin - Aripin, Norhartini (2014)
Communication Apprehension is believed as one of the negative precursors that hinder students to acquire English Language in ESL classroom. Specifically, this present study aims to investigate the affective factors; Fear of Making Mistakes, Students' Self-esteem and Students' attitude towards speaking contributing to communication apprehension (CA) in ESL classroom from the perspectives of gender, locality and English usage .A total of 199 bachelor students of a public university in Kelantan were Evolved in the study A set of questionnaire that was constructed by the researcher was used to collect data and data analysis was carried out with the help of SPSS Version 20.0. Results indicated that the level of communication apprehension in ESL classroom among the participants was moderately high. In the perspective of gender, locality and English Usage determined by T-test, it was found that there was no significant difference between communication apprehension and gender and locality, whereas there was significant difference between communication apprehension and English usage of the respondents. The result also reveals that communication apprehension and MUET speaking performance (score) was not strongly correlated as the data of correlation analysis indicated weak relationship between these variables. Finally, the coefficient analysis predicted a positive significant relationship between communication apprehension and students' self esteem in ESL classroom. However, there was no significant relationship between communication apprehension and the factors of Fear of making mistakes and Students' attitude towards speaking. From the study, it was recommended that further studies should examine the other factors pertaining psychological and social with the larger population and different groups of students as well, cutting across other institutions apart from specialized university.